Microevolutionary change in viscerocranial bones under congeneric sympatry in the Lake Tanganyikan cichlid genus Tropheus - Michaela Kerschbaumer; Lisbeth Postl; Christian Sturmbauer (Hydrobiologia, 2021)
The endemic Lake Tanganyika cichlid genus Tropheus lives at rocky shores all around the lake and comprises six species which are subdivided into about 120 morphologically similar but color-wise distinct populations. Typically, they live without a second Tropheus species, but there are some regions where two or even three sister species live in sympatry. We previously showed that there are morphological differences concerning head shape, eye size and insertion of fins among populations living alone compared to those living in sympatry with a second Tropheus . This study goes one step further to test if sympatry affects the shape of viscerocranial bones. By means of geometric morphometrics, we compare the shape of four bones among thirteen Tropheus populations, some of which in sympatry and some living alone. We quantify patterns of shape variation and estimate morphological disparity among the four bony elements in the study species and populations. We found consistent differences in the shape of one bony element among non-sympatric and sympatric populations, besides an extensive variation in the shape of viscerocranial bones within and among species. Furthermore, sexual dimorphism in Tropheus is clearly evident in the viscerocranial bones analyzed. We suggest that the relatively subtle morphological signal in sympatric vs. non-sympatric Tropheus populations is owed to the fact that the depth segregation does not yet represent a full shift in the trophic niche, albeit our data confirm that differences in ecologically relevant traits, such as bones of the preorbital region, play an important role in the process of niche separation and in the context of explosive diversification of cichlid fishes.

Morphological distinctness despite large-scale phenotypic plasticity—analysis of wild and pond-bred juveniles of allopatric populations of Tropheus moorii - Michaela Kerschbaumer; Lisbeth Postl; Martin Koch; Thomas Wiedl; Christian Sturmbauer (The Science of Nature, 2011)

Variation of territory size and defense behavior in breeding pairs of the endemic Lake Tanganyika cichlid fish Variabilichromis moorii - Christian Sturmbauer; Christoph Hahn; Stephan Koblmüller; Lisbeth Postl; Danny Sinyinza; Kristina M. Sefc (Hydrobiologia, 2008)